Study in ionic balance affecting nutrient uptake by corn - Silva, Filomena Leonor I. M. da; Fernandes, Manlio S.; Magalhães, José Ronaldo (Pesquisa Agropecuaria Brasileira, 2014)
In order to study the balance of ions and its effect on nutrient uptake, maize plants (Zea mays L.) were grown in pots under greenhouse conditions, in two soils, a Brunizem (silt loam) and a Hydromorphic série Ecologia (sandy soil) largely differing in texture, buffering power, nutrient content and pH. Nitrogen was applied either with or without the nitrification inhibitor N-SERVE and split in three applications during plant growth. Plants were harvested 28, 43 and 58 days after planting. In general, the plants grew better in the Brunizem without N-SERVE, while those grown in the Hydromorphic showed better growth when N-SERVE was applied. The physical characteristics of both soils influenced the root parameters, thus affecting the absorption of ions. The use of the nitrification inhibitor per se did not greatly change the root morphology or other parameters related to root development. The root cation exchange capacity (CEC) did not change greatly during the experimental period and no significant differences seem to appear between the two experiments. The correlations were in general similar for all nutrients studied.